Pembelajaran Kitab Amtsilati Dalam Meningkatkan Bakat Dan Minat Membaca Kitab Kuning Santri - Munif, Muhammad; Rozi, Fathor; Tusshalihah, Rofika (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Learning the yellow book has many benefits, especially in understanding religious knowledge. Which learning mostly uses the classical yellow book, because many Muslim scientists and intellectuals refer to the yellow book. This research uses a qualitative approach with case studies. The research method used is qualitative. With data collection techniques in the form of observation (observation), interviews (interviews) and documentation. This study aims to describe the implementation of the amtsilati book method in increasing students' aptitude and interest in reading the yellow book, in the Zaid Bin Tsabit (K) Putri Region and also to understand and examine events and problems that occur in the field. The subjects in this study were participants of the Takhossus Diny Bahrul Ulum amtsilati. The results of the research show that there are several tricks in increasing students' talents and interest in reading the yellow book, resulting in the following: First, providing volumes of amtsilati learning material in the form of teaching and learning activities (KBM) starting from volumes 1-5 and additional material in the form of Qoidati, Tatimmah, Sharfiyah. Second, teaching practice learning (Amtsilati Theory Practice). Third, the deposit of koidah and khulashoh amtsilati. Fourth, Discussion or joint deliberation (Munaqosah) on amtslati material. Fifth, Demonstration of amtsilati.